2017
DOI: 10.1093/biomet/asx026
|View full text |Cite
|
Sign up to set email alerts
|

Non-strange weird resampling for complex survival data

Abstract: This paper introduces the new data-dependent multiplier bootstrap for non-parametric analysis of survival data, possibly subject to competing risks. The new resampling procedure includes both the general wild bootstrap and the weird bootstrap as special cases. The data may be subject to independent right-censoring and left-truncation. We rigorously prove asymptotic correctness which has in particular been pending for the weird bootstrap. As a consequence, pointwise as well as time-simultaneous inference proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…But in cases, where this is so, the deviance is only very small. The phenomenon, that standard normal multipliers yield a worse performance than those with skewness equal to one, is in line with the findings in a revised version of Dobler et al (2015) where also heuristic theoretic arguments for a second-order correctness of both superior resampling procedures are provided. As there is, all in all, not much of a difference between the simulated coverage probabilities of the centered unit Poisson wild bootstrap and the weird bootstrap, we only focus on the results of the Poisson choice.…”
Section: Small Sample Behavioursupporting
confidence: 78%
See 1 more Smart Citation
“…But in cases, where this is so, the deviance is only very small. The phenomenon, that standard normal multipliers yield a worse performance than those with skewness equal to one, is in line with the findings in a revised version of Dobler et al (2015) where also heuristic theoretic arguments for a second-order correctness of both superior resampling procedures are provided. As there is, all in all, not much of a difference between the simulated coverage probabilities of the centered unit Poisson wild bootstrap and the weird bootstrap, we only focus on the results of the Poisson choice.…”
Section: Small Sample Behavioursupporting
confidence: 78%
“…This resampling scheme corresponds to choosing ξ j i`1 " BinpY pX i q, maxp1, Y pX i qq´1q, where X i is the censoring or event time of individual i, whichever comes first. This is a particular choice of the data-dependent multiplier bootstrap of Dobler et al (2015). In their article, heuristic arguments for the second order correctness under absolute continuity of the data have shown that centered unit Poisson variates and weird bootstrap multipliers perform favorably in comparison to standard normal wild bootstrap weights.…”
Section: Now An Appropriate Wild Bootstrap Version Ofmentioning
confidence: 99%
“…Since the minimally selected test statistics in our paper do not have a nice martingale representation form and are not normally distributed, the wild bootstrap method of Lin (1997) is not applicable to our setting. The weird bootstrap and its extensions (Andersen et al, 2012; Dobler et al, 2017) consider the Nelson–Aalen estimator, and replace the counting process increments at time t with binomial random variables with size Y ( t ) and success probability d  ( t ), where Y ( t ) is the size of risk set at t and d  ( t ) is the empirical hazard function at t . It is possible that we could generate a weird bootstrap replication through this process – under the null of quasi-independence – and use it to form a reference distribution for our test statistics.…”
Section: Discussionmentioning
confidence: 99%
“…() as well as Dobler et al. () recently gave a thorough mathematical treatment of this approach also allowing for independent left‐truncation and general multipliers. Extensions to more complex multistate models are, however, rare in the current literature.…”
Section: Introductionmentioning
confidence: 99%